The »Borders of the Land of Canaan« Document (Num 34:1–12): Its Context in the Book of Numbers and Its Reflection in the Book of Joshua - Kisleṿ, Itamar (Hebrew bible and ancient Israel, 2023)
In the context of the debate regarding the date, nature, and scope of the Priestly writings, the book of Numbers and its role in the formation of the Pentateuch has received much attention. Investigation of the relationship between the chapters that treat the settlement in the land of Canaan in Numbers and Joshua is crucial for the assessment of the place of the book of Numbers in the compositional process of the Pentateuch. I propose here to examine the scholarly stances on this issue in light of the literary similarity between two passages in Numbers and Joshua: the southern border of the land of Canaan (Num 34:3-5) and the southern Judahite border (Josh 15:1b-4).